Bonjour ! je n'arrive pas à faire l'exercice ci-dessous:
Développe et réduis les expressions:
A= 11+2(x-6)+4(-3y-6)
B=-2(x-5)-3(7-4x)
C=8+2y-5(2y-6)+4
D=-7y-4(3y-6)+3+2(3y-7)
E= -5z+5z(z-3)-7(6-8z)
Voilà, merci d'avance !

1

Réponses

2014-06-02T18:58:58+02:00
Développe et réduis les expressions :

A = 11 + 2 (x - 6) + 4 (-3y - 6)
A = 11 + 2x - 12 - 12y - 24
A = 2x - 12y + 11 - 12 - 24
A = 2x - 12y - 25

B = - 2 (x - 5) - 3 (7 - 4x)
B = - 2x + 10 - 21 + 12x
B = - 2x + 12x + 10 - 21
B = 10x - 11

C = 8 + 2y - 5 (2y - 6) + 4
C = 8 + 2y - 10y + 30 + 4
C = 2y - 10y + 8 + 30 + 4
C = - 8y + 42

D = - 7y - 4 (3y - 6) + 3 + 2 (3y - 7)
D = - 7y - 12y + 24 + 3 + 6y - 14
D = - 7y - 12y + 6y + 24 + 3 - 14
D = - 13y + 13

E = - 5z + 5z (z - 3) - 7 (6 - 8z)
E = - 5z + 5z² - 15z - 42 + 56z
E = 5z² - 5z - 15z + 56z - 42
E = 5z² + 36z - 42